Bounce - Friend, Natasha, 1972- (New York : Scholastic Press, 2007)
Thirteen-year-old Evyn's world is turned upside-down when her father, widowed since she was a toddler, suddenly decides to remarry a woman with five children. Ev, her father and brother move from Maine to Boston, where she is enrolled in private school.
Keywords: Stepfamilies -- Juvenile fiction; Remarriage -- Juvenile fiction; Schools -- Juvenile fiction; Popularity -- Juvenile fiction; Families -- Massachusetts -- Juvenile fiction; Moving, Household -- Juvenile fiction; Massachusetts -- Juvenile fiction